Control of cutaneous leishmaniasis caused by Leishmania major in south‐eastern Morocco. Issue 10 (7th June 2015) - Bennis, Issam; De Brouwere, Vincent; Ameur, Btissam; El Idrissi Laamrani, Abderrahmane; Chichaoui, Smaine; Hamid, Sahibi; Boelaert, Marleen
Abstract Objective The incidence of cutaneous leishmaniasis (CL) caused by Leishmania major has increased in Morocco over the last decade, prompting the Ministry of Health to take intersectoral response measures including vector and reservoir control. The aim of this article was to describe the CL outbreak response measures taken in the province of Errachidia, where the reservoir of L. major, a sand rat (Meriones shawi), was targeted using strychnine‐poisoned wheat baits from 2010 to 2012. Method We analysed routine surveillance data and other information using the data of the CL control programme. Results We present data on the evolution and the extension of CL in this province as well as the epidemiological profile of the disease. Between 2004 and 2013, 7099 cases of CL were recorded in Errachidia Province, gradually affecting all districts. Our results demonstrate that more women were affected than men and that all age groups were represented. Conclusion Errachidia Province was the epicentre of the recent CL outbreak in Morocco. A notable decline in incidence rates was observed after 2011. The outbreak control measures may have contributed to this decline, as well as climatic trends or progressing herd immunity.